Стратегия «Damage control» - Костырной, А.В.; Поленок, П.В. (Таврический медико-биологический вестник, 2011)
Розробленї показання та способи реалiзацiї оперативного лiкування гострої абдомiнальної патологiї в режимi damage control. Створена власна шкала для оцiнки оперативного ризику та прогнозу захворювання на пiдставi фiзiологiчного статусу пацiєнта. Впроваджено в практику лапаростомiчна конструкцїiя для контролю за станом органiв черевної порожнини. Застосування тактики damage control дозволило знизити летальнiсть вiд гострої абдомiнальної патологiї на 16 %. Indications and methods of realization for operative treatment in case of acute abdominal pathology in the concept of damage control surgery were made. Physiologic and operative severity score for the enumeration of mortality and morbidity was created. Laparostomic construction for damage control of abdominal cavity was invented. . Lethality at acute abdominal pathology has reduced on 16% with adaptation of damage control.